Model Komunikasi Child-Centred Care dalam Radiodiagnostik Anak sebagai Upaya Pengurangan Kecemasan, Paparan Ulang dan Burnout Keluarga - Gede Agus Susila Dharma,S.TR.Kes; Prof.Dr. I Gusti Ayu Putri Kartika, S.H,M.H (Jurnal Hukum Lex Generalis, 2026)
Pediatric radiodiagnostic services raise legal, ethical and psychological issues because they may cause anxiety, repeated radiation exposure and family burnout. The implementation of Child Centred Care (CCC) must align with legal norms and the principle of the best interest of the child (BIC). This normative legal study analyzes CCC through legislation, legal doctrines, academic literature, scientific journals and court decisions. The discussion shows that CCC supports children’s rights, reduces anxiety, minimizes radiation exposure and decreases family burnout. CCC is a legal obligation that requires stronger regulation, protocols, institutions and medical staff training.